2017
DOI: 10.1037/apl0000174
|View full text |Cite
|
Sign up to set email alerts
|

Comparing integral and incidental emotions: Testing insights from emotions as social information theory and attribution theory.

Abstract: Studies have indicated that observers can infer information about others' behavioral intentions from others' emotions and use this information in making their own decisions. Integrating emotions as social information (EASI) theory and attribution theory, we argue that the interpersonal effects of emotions are not only influenced by the type of discrete emotion (e.g., anger vs. happiness) but also by the target of the emotion (i.e., how the emotion relates to the situation). We compare the interpersonal effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 75 publications
1
56
0
Order By: Relevance
“…Entrepreneurial passion is likely to be recognizable by others (Hatfield et al, 1994; Sullins, 1991), because most passionate entrepreneurs display their passion to the people around them, act with passion, and express their passion for entrepreneurial activities (Cardon, 2008). The contagion of entrepreneurial passion, like the contagion of other emotional states, can be triggered by emotional and cognitive cues (Hillebrandt & Barclay, 2017; Kelly & Barsade, 2001) and can include subconscious and conscious processing (Hess & Fischer, 2013).…”
Section: Entrepreneurial Passion and Its Contagionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurial passion is likely to be recognizable by others (Hatfield et al, 1994; Sullins, 1991), because most passionate entrepreneurs display their passion to the people around them, act with passion, and express their passion for entrepreneurial activities (Cardon, 2008). The contagion of entrepreneurial passion, like the contagion of other emotional states, can be triggered by emotional and cognitive cues (Hillebrandt & Barclay, 2017; Kelly & Barsade, 2001) and can include subconscious and conscious processing (Hess & Fischer, 2013).…”
Section: Entrepreneurial Passion and Its Contagionmentioning
confidence: 99%
“…Due to the effect of positive affect on employees (Forgas & George, 2001; Vallerand et al, 2007), perceptions of entrepreneurs’ passion should also influence employee goal commitment, and more performance-related outcomes such as effort and creativity, which are highly important for entrepreneurial activity. Employee perceptions of entrepreneurs’ passion influence their appraisals of whether or not entrepreneurial activities are pleasant (Hillebrandt & Barclay, 2017; Peters & Kashima, 2015) and serve as a signal that the entrepreneurial tasks are of great importance, such that employees become committed to the tasks’ goals, leading to goal commitment. When employees feel and understand the tasks’ importance, they are more likely to put extra effort into their work (Foo et al, 2009).…”
Section: Effects Of Employee Perceptions Of Entrepreneurs’ Passion Onmentioning
confidence: 99%
“…Finally, state affect in this study was manipulated using incidental emotions, which were unrelated to that situation. Future research may as well find a different pattern in the results if these emotions arose from a decision at hand (integral emotion; Lerner et al, 2015 ; Hillebrandt and Barclay, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…In the negotiation literature, most studies are concerned with integral affect since they have shown to convey more strategic information and thus have a stronger influence on the recipients’ judgments and behavior ( Van Kleef, 2016 ; Hillebrandt and Barclay, 2017 ). Recent studies have shown that incidental emotions have stronger intrapersonal carry over than integral emotions ( Schwarz and Clore, 1983 ; Lerner et al, 2015 ; Van Kleef, 2016 ).…”
Section: The Role Of Emotions In Shaping Decisions: An Appraisal-tendmentioning
confidence: 99%
“…People may also use emotions and feelings as sense-making data. Management scholars have recently applied attribution theory to explain how negotiators attributed perceived threat and cooperativeness to their counterparts' emotions (Hillebrandt and Barclay 2017), how individuals' varied attributions of supervisor behavior led to different emotions and behavioral responses (Oh and Farh 2017), and how the attribution of external or internal locus of control could explain stakeholders' perception of foreign organizations (Crilly et al 2016). The premise that VBM draws from attribution theory is that people square their experiences or proactively anticipate future encounters using resources, such as personal values, that they currently have.…”
Section: First Element (Pre-negotiation): What Are My Values?mentioning
confidence: 99%